KEDUDUKAN NEGARA SEBAGAI KREDITOR ATAS UTANG PAJAK DAN PINJAMAN BADAN USAHA MILIK NEGARA (BUMN) DALAM PERSPEKTIF HUKUM KEPAILITAN DI INDONESIA - ADIONO, YOSEP BAYU (Jurnal HUKUM BISNIS, 2026)
Bankruptcy in State-Owned Enterprises (SOEs) has raised debates, especially regarding the position of the State as a creditor of tax debts, subsidies, and loans. In practice, bankruptcy not only involves the relationship between debtors and private creditors, but also involves the State's fiscal interests stemming from tax obligations and various forms of public financing. A fundamental issue arises when the bankruptcy estate of an SOE is insufficient to pay off all obligations, necessitating a determination of the priority order of payment among creditors. At this point, the question arises whether State creditors with claims on taxes and loans have a higher position than private creditors, including other secessionist and preferred creditors. Bankruptcy law in Indonesia through Law No. 37/2004 on Bankruptcy and PKPU (Bankruptcy Law), the Civil Code, and tax regulations provide a legal basis for the classification of creditors, namely separatist, preferred, and concurrent creditors. However, the position of the State's debt in this structure is still subject to various interpretations. Tax debts are explicitly classified as State receivables that enjoy preferential rights, but these rights remain under the position of separatist creditors that have material security. Meanwhile, the position of loans and subsidies from the State to SOEs has not been strictly regulated, giving rise to potential legal uncertainty in the bankruptcy process. This research is a normative legal research through a statutory approach and conceptual approach. Keywords: BUMN, Creditors, Bankruptcy, Priority of Payment.